Training Making Materials Video Interactive Learning For Teachers in SMK Negeri 1 Muara Enim - Sri Desy Siswanti; Darmawijoyo Darmawijoyo; Saparudin Saparudin; Syamsuryadi Syamsuryadi; Ahmad Fali Oklilas; Hadi Purnawan Satria; Anggina Primanita (Annual Research Seminar (ARS), 2015)
Report on the implementation of community service describes the learning outcomes of the training video creation intended for Vocational High School (SMK) Negeri 1 Muara Enim. The training was attended by 66 teachers. This training provides a solution to improve the teaching of teachers SMK 1 Muara Enim is by making instructional materials in the form of video lessons. The training is carried out with extension methods and practices, to support the training is complemented every teacher training modules in softcopy. The training was held at the Hall of SMK 1 Muara Enim. To measure the result of performance evaluation activities, where the outcome is a matter of understanding of the material by the participants, the average value reached approximately 80-100 giving the correct answer. For the future need this kind of training activities with the broader material and a longer period  with the aim to improve the quality of teaching and school teachers.